The Effects of Cervus elaphus Aquapuncture and Ginseng Radix Aquapuncture on the Growth of Animals - Lee, Jin-Man; Kim, Young-Tae; Lee, Hak-In; Son, Yang-Sun; Jin, Soo-Hee; Lee, Hyang-Sook; Park, Hi-Joon; Lee, Hye-Jung; Lim, Sa- (Korean Pharmacopuncture Institute, 2000)
The effects of Cervus elaphus aquapuncuture and Ginseng Radix aquapuncuture on the growth, protein efficiency ratio, contents of total protein, total cholesterol, and triglyceride in serum were studied for thirty four days. The results were summarized as follows. 1. Weight significantly increased in 0.3% Cervus elaphus aquapuncture group on Chunchu loci and in 0.2% Ginseng Radix aquapuncture group on Chunchu loci compared to normal saline aquapuncture group on Chunchu loci. 2. Protein efficiency ratio significantly increased in 0.2% and 0.3% of Cervus elaphus aquapuncture group on Chunchu loci and 0.1%, 0.2% and 0.3% of Ginseng Radix aquapuncture group on Chunchu loci compared to nonnal saline aquapuncture on Chunchu loci. 3. Total protein significantly increased in 0.2% and 0.3% of Cervus elaphus aquapuncture group on Chunchu loci compared to nonnal saline aqriapuncture On Chunchu loci. whereas it had a tendency to increase in 0.2% Ginseng Radix aquapuncture group on Chunchu loci compared to normal saline aquapuncture group on Chunchu loci. 4. Total cholesterol increased a little in 0.3% Cervus elaphus aquapuncture group on Chunchu loci compared to normal saline aquapuncture group on Chunchu loci. 5. Triglyceride significantly increased in 0.2% Ginseng Radix aqua puncture group on Chunchu loci compared to normal saline aquapuncture group on Chunchu loci. Significance was acknowledged in the effect by density difference of medicines. In the Cervus elaphus group, there was the most significant increase in density of 0.3% aquapuncture, whereas in Ginseng Radix group, there was the most significant increase in density of 0.2% aquapuncture. So setting up density of medicines is important and many various studies for clinical application are required.